2021
DOI: 10.1111/add.15487
|View full text |Cite
|
Sign up to set email alerts
|

Opioid use disorder and overdose among youth following an initial opioid prescription

Abstract: Background and Aims Some adolescents and young adults (termed “youth”) prescribed an opioid will develop opioid use disorder or experience overdose. This study aimed to identify patient and prescription characteristics associated with subsequent risk of opioid use disorder or overdose during the year after an opioid is first dispensed. Design Retrospective cohort study. Setting Commercial health insurance claims in a large United States (US) database from 2006 to 2016. Participants Youth age 11 to 25 years fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
(72 reference statements)
0
15
1
Order By: Relevance
“…No opioids were prescribed for patients with dental pain in the past 12-months in HDUC. Considering that about 1,800 patients received prescriptions of more than 20,000 pills of opioids annually in this clinic alone before we introduced our opioid reduction initiatives 22 , reducing the reliance on opioids for acute dental pain is particularly salient in light of a persistent OUD crisis 2,38,39 . Population-based cohort studies found that 2 - 7% of the patients receiving a dental opioid prescription would develop new and persist use of opioids within one year 9-11 .…”
Section: Discussionmentioning
confidence: 99%
“…No opioids were prescribed for patients with dental pain in the past 12-months in HDUC. Considering that about 1,800 patients received prescriptions of more than 20,000 pills of opioids annually in this clinic alone before we introduced our opioid reduction initiatives 22 , reducing the reliance on opioids for acute dental pain is particularly salient in light of a persistent OUD crisis 2,38,39 . Population-based cohort studies found that 2 - 7% of the patients receiving a dental opioid prescription would develop new and persist use of opioids within one year 9-11 .…”
Section: Discussionmentioning
confidence: 99%
“…23 Indeed, while thresholds such as 50 or 90 MME/day are simpler for analysis and policy approaches, the risk of adverse events is linear to the dose of opioids dispensed and potentiated by many factors other than the opioid daily dose. 16,18,20,23,38 The percentage of persons 12-18 years old receiving ≥90 MME daily (3.4% in 2017) is overall low and may be reasonable in patients with painful chronic conditions or opioid tolerance. 34 Additional analyses with data that contain diagnostic information would allow ascertainment of whether the roughly 25% of adolescents who received ≥50 daily MME did so for appropriate diagnoses or under appropriate conditions.…”
Section: Discussionmentioning
confidence: 99%
“…While the absolute numbers of opioid-naïve adolescents receiving ER/LA opioids is not large (n = 40 in Q4 of 2017), the greater average daily MME of these preparations places opioid-naïve adolescents who receive ER/LA opioids at elevated risk of adverse events, especially early after initiation of therapy. 18,40,41 Adult data demonstrate that ER/LA opioids are associated with a greater risk of overdose events particularly in the first 2 weeks of use, and 24% of adult patients who received ER/LA preparations received them for acute pain. 42,43 Pediatric data also demonstrate that the use of ER/LA opioids by opioid naïve adolescents and young adults is associated with double the adjusted odds (AOR 2.01) of experiencing an opioid overdose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations